1999
DOI: 10.1056/nejm199905273402103
|View full text |Cite|
|
Sign up to set email alerts
|

Benefit of Abciximab in Patients with Refractory Unstable Angina in Relation to Serum Troponin T Levels

Abstract: The serum troponin T level, which is considered to be a surrogate marker for thrombus formation, identifies a high-risk subgroup of patients with refractory unstable angina suitable for coronary angioplasty who will particularly benefit from antiplatelet treatment with abciximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
144
2
12

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 626 publications
(164 citation statements)
references
References 19 publications
6
144
2
12
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23] The majority of these included elevated cardiac markers and ECG changes as independent predictors of adverse outcomes. Unfortunately, there are limited data on risk assessment of "subacute" patients with ACS after initial presentation.…”
Section: Timing Of Heart Rate Assessmentmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23] The majority of these included elevated cardiac markers and ECG changes as independent predictors of adverse outcomes. Unfortunately, there are limited data on risk assessment of "subacute" patients with ACS after initial presentation.…”
Section: Timing Of Heart Rate Assessmentmentioning
confidence: 99%
“…Multiple studies have shown that patients with an elevated troponin level are at increased risk. 1,[5][6][7] There appears to be a direct relationship between the degree of troponin elevation and mortality. 5 Interestingly, recurrent MI appears to be very high among patients with low levels of troponin elevation, and thus the rate of death or MI appears to be equally high in patients with either low or high troponin values.…”
Section: Cardiac Biomarkersmentioning
confidence: 99%
“…7 The European Society of Cardiology (ESC)/ACC consensus document on MI, as well as multiple trials in UA/NSTEMI, supports a very low cut-point for troponin elevation as a biomarker of adverse outcome in patients presenting with a clear history of ischemic symptoms. 1,[5][6][7][8] It should be noted however, that in patients without a clear history, troponin elevations in the absence of ischemia have been reported 9,10 and can be caused by congestive heart failure, 11 pulmonary embolism, 12 or technical problems with the assay. 10 Thus, in patients with an unclear history, small troponin elevations may not be diagnostic of acute coronary syndromes (ACS).…”
Section: Cardiac Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations